Acceptance of Papillomavirus Vaccination among Females in Al-leith Province, Saudi Arabia - Alomari, Hajar; Al-Hasnani, Shatha; Almahdawi, Layla; Alzahrani, Afrah; Elawad, Mohammed (European Scientific Journal, ESJ, 2024)
A community-based study was carried out among females in Al-leith province, Saudi Arabia to identify the acceptance of females to be vaccinated against Human Papillomavirus (HPV). We interviewed 315 females in ages from 11 to 26, the target group of HPV vaccination. The relevant data were collected using a simple questionnaire. The findings illustrated that majority of participants were in age group (15 – 26 years), the actual target of vaccination against HPV, most of participants were Saudi females, and most of them were not married. It was found that less than half (43.8%) of females were willing to receive the vaccine, and the rest of the total females did not accept vaccination. The study concluded that still high percentage of females in Saudi Arabia did not accept vaccination against Human papillomavirus, the issue that need more efforts to increase the percentage of vaccination acceptance.